Christmas amnesia - Scott, Laura, 1961- (Scott, Laura, 1961- Callahan confidential., 2017)
Assaulted a week before a high-profile drug trafficking trial, assistant district attorney Madison Callahan narrowly escapes death<U+2026>but suffers amnesia. Now, when she can't recall the identity of her attacker, everyone is suspect<U+2014>except the handsome policeman who saved her. Officer Noah Sinclair will do anything to bring the mob-connected drug trafficker to justice, including provide personal protection to Madison<U+2014>the sister of the partner he nearly got killed. But helping her regain her memory may end their unlikely alliance because once she remembers him, Noah might be the last man she'll want to rely on. As the trial looms and the assailant dead set on ensuring that Madison doesn<U+2019>t survive to see Christmas, it'll take everything Noah<U+2019>s got to keep Madison alive.